The Problem of Ingrown Toenail in Children - I.P. Zhurilo; V.K. Litovka; G.A. Sopov; K.V. Latyshov; I.N. Inozemtsev (Zaslavsky O.Yu., 2012)
The results the treatment of children with the ingrown toenail are analyzed and presented in this article. The 329 children aged from 4 to 17 years were treated in the regional children's clinical hospital of Donetsk for last twenty years. The clinical picture of disease is described. Indications for surgical and conservative treatment were considered.